2011
DOI: 10.1038/onc.2011.537
|View full text |Cite
|
Sign up to set email alerts
|

Transtumoral targeting enabled by a novel neuropilin-binding peptide

Abstract: We have recently described a class of peptides that improve drug delivery by increasing penetration of drugs into solid tumors. These peptides contain a C-terminal Cend Rule (CendR) sequence motif (R/K)XX(R/K), which is responsible for cell internalization and tissue-penetration activity. Tumor-specific CendR peptides contain both a tumor-homing motif and a cryptic CendR motif that is proteolytically unmasked in tumor tissue. A previously described cyclic tumor-homing peptide, LyP-1 (sequence: CGNKRTRGC), cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
187
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(192 citation statements)
references
References 39 publications
(42 reference statements)
5
187
0
Order By: Relevance
“…expressed, were used as the models of tumor cells and tumor neovascular endothelial cells, respectively. 20,22,23,47,48 Low cytotoxicity of the carrier itself is a primary concern in the development of a drug delivery system. Figure 6A and B shows the viability of MDA-MB-231 cells and HUVECs incubated with HMSN, pHMSN, or tHMSN for 48 hours (as determined by CCK-8 assay).…”
Section: Evaluation Of Drug-loading and Drug-release Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…expressed, were used as the models of tumor cells and tumor neovascular endothelial cells, respectively. 20,22,23,47,48 Low cytotoxicity of the carrier itself is a primary concern in the development of a drug delivery system. Figure 6A and B shows the viability of MDA-MB-231 cells and HUVECs incubated with HMSN, pHMSN, or tHMSN for 48 hours (as determined by CCK-8 assay).…”
Section: Evaluation Of Drug-loading and Drug-release Propertiesmentioning
confidence: 99%
“…On the basis of the results for cellular uptake and cytotoxicity of the drug-loaded nanoparticles, it can be concluded that tHMSN could enhance endocytosis of cargoes and thereby mediating more robust cytotoxicity compared with pHMSN. Meanwhile, given the overexpression of NRP in many tumor cells and angiogenic blood vessel cells, [18][19][20] such an ability should have a degree of selectivity and dualtargeting performance.…”
Section: In Vitro Pharmacodynamic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified a peptide in our panel of tumor-homing peptides that specifically recognizes the fibroblasts that reside in early premalignant breast lesions. This peptide, iRGD, is prototype compound among the tumor-penetrating peptides we have described recently Roth et al, 2012;Alberici et al, 2012). Systemically injected iRGD homes to individual cells around the premalignant PyMT glands (Fig.…”
Section: Extracellular Matrix Alteration In Pre-malignant Lesionsmentioning
confidence: 99%
“…In such nanostructure (Figure 1), tLyp-1, a newly reported tumor-homing heptapeptide, 44 acted as a ligand selectively targeted to neuropilin protein (a membranous receptor that was overexpressed in many types of tumor cells 45 ) on the cell surface and thus succeeded in achieving active targeting and ligand-mediated endocytosis. Second, mesoporous silica, a porous nanostructural biomaterial that allows for high drug loading capacity and attachment of different functional groups, was introduced to protect and shield the GNRs against their self-aggregation as well as be loaded with imaging agent and be decorated with functional peptide.…”
Section: Introductionmentioning
confidence: 99%